Pengaruh Knowledge terhadap Talent Management bagi Calon Pekerja - Aulika Dwi Priscilla; Zahra Amelia Anwar Nst; Dara Nursusana Padang; Feronica Simanjorang (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to investigate the impact of students' knowledge levels in the Library and Information Science program on their talent management as future job seekers. In an increasingly information-driven era, students' knowledge and competencies play a pivotal role in preparing them for success in the job market. The research methodology employed is a case study involving students in the Library and Information Science program as the sample. Data was collected through questionnaires and interviews with students and faculty to understand how their knowledge influences the talent management process. Data analysis was conducted using both qualitative and quantitative approaches. The results of the study indicate that the knowledge acquired by students in the Library and Information Science program significantly influences their talent management process. Students with broader and deeper knowledge tend to be better prepared and more confident in managing their talents. Interviews also revealed the pivotal role of faculty in assisting students in developing their knowledge and talents.